Impact of university brand awareness on students’ admission decisions: Cross-cultural analysis - Liu, Yishu (Edelweiss Applied Science and Technology, 2025)
University brand awareness significantly influences students' admission decisions. Existing studies often lack a cross-cultural perspective due to sample geographic limitations and insufficient analytical methods. This study adopts a mixed-method design and constructs a cross-cultural analytical framework. It integrates global university brand data (e.g., QS rankings, social media index, academic influence) and applies natural language processing to extract brand image characteristics. Key decision variables are identified through a transnational education survey, and then factor analysis and structural equation modeling (SEM) are conducted to quantify the impact of brand awareness. Multi-group analysis reveals cross-cultural path differences. Cluster analysis reveals different brand sensitivities. The results show that East Asian students scored 80 points in long-term orientation, which is significantly different from students in other regions (p=0.0348), highlighting the impact of culture on brand influence. This study promotes brand management in higher education and provides strategies for international brand building, social media engagement, and academic collaboration to attract diverse students. It provides practical insights for precise and culturally customized admissions efforts.